A Raw Material Truck’s Queue System Optimization: Optimasi Sistem Antrian Bongkar Muat Truk Bahan Baku - Prayitno, Sugeng; Sulistiyowati, Wiwik (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates strategies to enhance efficiency in the unloading process of raw materials, crucial for maintaining productivity in paper production. Through field observations, a queuing system analysis employing a multi-channel single phase type was conducted. Results indicate that adding one unloading team can significantly reduce truck queuing time from 33 to 17 minutes. This finding underscores the potential for operational optimization through strategic resource allocation, emphasizing the importance of service quality alongside pricing in supplier engagement strategies for industrial enterprises Highlights : The study explores strategies to enhance efficiency in the unloading process of raw materials. Results indicate a significant reduction in truck queuing time through the addition of one unloading team. Emphasis is placed on the importance of service quality and pricing in supplier engagement strategies for industrial enterprises. Keywords: Efficiency, Queuing System, Raw Materials, Optimization, Supplier Engagement